1983
DOI: 10.1002/ccd.1810090103
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative coronary angiography during intracoronary streptokinase in acute myocardial infarction: How long to continue thrombolytic therapy?

Abstract: An intracoronary infusion of streptokinase is often administered in patients with acute myocardial infarction. To address the question of how long intracoronary streptokinase should be infused, we studied 13 patients with symptoms and electrocardiographic findings suggesting an evolving myocardial infarction. We used subselective catheterization techniques and made quantitative angiographic measurements of the percentage of reduction of coronary artery (CA) diameter before intracoronary streptokinase therapy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This failure to fully recanalize to the dimensions of the original stenosis has at least four possible explanations: First, the thrombolytic infusion may not have been continued long enough. Feldman et al 24 have shown an improvement in stenosis severity with continued streptokinase infusion to as long as 180 min. Our resistance data suggest that active recanalization continues for at least 60 min after the time of first visualization (see figure 7).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This failure to fully recanalize to the dimensions of the original stenosis has at least four possible explanations: First, the thrombolytic infusion may not have been continued long enough. Feldman et al 24 have shown an improvement in stenosis severity with continued streptokinase infusion to as long as 180 min. Our resistance data suggest that active recanalization continues for at least 60 min after the time of first visualization (see figure 7).…”
Section: Discussionmentioning
confidence: 97%
“…Harrison et al',5 without making the distinction between the "original" and "recanalized" lumen, observed that lumen area of less than 0.4 mm2 (0.7 mm mean diameter) after infusion of streptokinase predicted eventual reocclusion. Finally, Sheehan et al [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] have determined that improvement of myocardial contractile function does not occur if residual stenosis lumen diameter measured by the above method is less than 0.4 mm.…”
Section: Discussionmentioning
confidence: 99%